On Sets with Extremely Big Slices - Ivakhno, Ye. (Журнал математической физики, анализа, геометрии, 2006)
A new characterization of the Radon-Nikodym property in terms of sizes of slices and equivalent norms is presented. A property opposite to the Radon-Nikodym property is studied in the context of 1-unconditional sums of Banach spaces.